The Two Tests: The Supernatural Claims of Christianity Tried by Two of Its Own Rules - Lisle, Lionel (Salt Lake City, UT : Project Gutenberg, 2011)
"The Two Tests: The Supernatural Claims of Christianity Tried by Two of Its Own" by Lionel Lisle is a treatise that critically examines the supernatural claims of Christianity, written in the late 19th century. The book delves into the validity of the Christian faith through the lens of modern thought, questioning the historical and supernatural narratives presented in the New Testament, particularly those concerning the birth and miracles of Jesus Christ. Lisle seeks to explore the evidence surrounding these claims, advocating for a reasoned approach to belief and religious inquiry. The opening of the text introduces Lisle's rationale for the inquiry into Christian beliefs, emphasizing his intention to aid those who struggle with doubt regarding their faith. With reference to previous thinkers like Dr. Chalmers and Dean Stanley, he critiques the reliability and credibility of testimonies about supernatural events, such as the birth of Jesus and the accounts of his miracles. He poses pressing questions about the integrity of the narratives provided by the Gospel writers, particularly focusing on the lack of consistent eyewitness testimonies and the conflicts between their accounts. Lisle's analytical approach sets the stage for a thorough examination of Christian doctrine, prompting readers to reflect on the foundations of their beliefs through the critical evaluation of evidence. (This is an automatically generated summary.)
Release date is 2011-12-22
Produced by David Widger
Keywords: Apologetics